STUDY OF RESISTANCE DURING COVERING OF SOWING CROPS INTO THE SEED FERTILIZER PIPE - Беседа, А. А. (Scientific Progress & Innovations, 2015)
The work is devoted to the study of the movement of seed under the action of gravity in sowing system, namely «sowing system – seed fertilizer pipe – guiding device – undertenon space of dovetail ploughshare – switchgear». The impact of resistance during the flow of seed on the example of winter wheat was theoretically described, which is considered with regard to the form of profile of its convenient shape by flow in sow automate, provided mechanical feeder that is able to asume and theoretically describe the general scheme of seed movement in sowing system.